2012
DOI: 10.2105/ajph.2011.300548
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Racial/Ethnic Disparities in Children’s Dental Health: A Decomposition Analysis

Abstract: Objectives. We measured racial/ethnic inequalities in US children’s dental health and quantified the contribution of conceptually relevant factors. Methods. Using data from the 2007 National Survey of Children’s Health, we investigated racial/ethnic disparities in selected child dental health and preventive care outcomes. We employed a decomposition model to quantify demographic, socioeconomic, maternal health, health insurance, neighborhood, and geographic effects. Results. Hispanic children had the poorest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 31 publications
5
73
0
2
Order By: Relevance
“…However, like our study, many other studies have found less dental care in African-American children and adults when compared with Caucasians [7][8][9][10][11][12]. In 2004, the Medical Expenditure Panel surveyed 34,403 individuals.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, like our study, many other studies have found less dental care in African-American children and adults when compared with Caucasians [7][8][9][10][11][12]. In 2004, the Medical Expenditure Panel surveyed 34,403 individuals.…”
Section: Discussionsupporting
confidence: 55%
“…While African-Americans were less likely to report differences in accessing dental care than Caucasians, they visited the dentist less in the previous year [8]. The 2007 National Survey of Children's Health accounted socioeconomic status for 71% of the gap in preventive dental care between African-American and Caucasian children [9]. The type of dental insurance has not been found to affect preventive dental care in African-American children [12].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our selection of explanatory variables is motivated by several theories for determinants of health and racial disparities and by results from previous studies that have highlighted an important role for these variables. We appeal to general microeconomic and psychosocial theories that highlight the importance of education, prenatal care, geographic location/residential segregation, and other factors for child health and racial disparities (16,22,48,49,(51)(52)(53)(54)(55) and to previous studies (22,37,38,41,(56)(57)(58)(59)(60)(61)(62) when possible for selecting conceptually relevant explanatory variables. We choose the following model: (1) where for child i, H is health measured by either LBW (y=1) or PTB (y=2) and is a function of child ancestry (Ancestry), prenatal care (PNC), demographic characteristics (Dem), maternal health (Health), maternal fertility (Fertility), socioeconomic status (SES) and geographic effects (Area); u is the error term.…”
Section: Study Measures and Empirical Modelmentioning
confidence: 99%
“…This model is an extension of the Oaxaca-Blinder decomposition model to non-linear models for binary outcomes and has been successfully applied in previous studies. (56,(85)(86)(87) The model identifies the extent to which differences in a particular characteristic between two groups explains the difference in their outcomes, and has been previously used to explain racial health disparities in other contexts. (34,56) For each racial comparison (e.g., AO versus EO), the model first estimates equation (1).…”
Section: Disparity Decompositionmentioning
confidence: 99%
See 1 more Smart Citation